Electroacupuncture for tapering off long-term benzodiazepine use: A randomized controlled trial. (February 2019) - Yeung, Wing-Fai; Chung, Ka-Fai; Zhang, Zhang-Jin; Zhang, Shi-Ping; Chan, Wai-Chi; Ng, Roger Man-Kin; Chan, Connie Lai-Wah; Ho, Lai-Ming; Yu, Branda Yee-Man; Chau, Janet Ching-Sum; Lau, Novella Chi-Ling; Lao, Li-Xing
Abstract: Objective: To evaluate the efficacy of using electroacupuncture as an adjunct treatment in enhancing the benzodiazepine cessation rate in long-term benzodiazepine users. Methods: This was a randomized, assessor- and subject-blinded, controlled trial. One hundred and forty-four long-term benzodiazepine users were randomly assigned to receive either electroacupuncture or placebo acupuncture (a sham itervention using non-invasive placebo needles) combined with a gradual benzodiazepine tapering schedule for 4 weeks. The primary outcome was the cessation rate of benzodiazepine use. Subjects were assessed on their benzodiazepine usage, benzodiazepine withdrawal symptoms, insomnia severity, and anxiety and depressive symptoms at baseline, week 6 and week 16. Results: The cessation rates of the electroacupuncture and placebo acupuncture groups at 12 weeks post-treatment were 9.17% and 10.83%, respectively. Both groups showed a reduction in benzodiazepine usage by a self-completed drug record at week 16 (compared to baseline: electroacupuncture group −40.23% versus placebo acupuncture group −48.76%). However, no significant between-group differences were found in the benzodiazepine cessation rate, reduction in benzodiazepine usage, and other secondary measures across all the study time points. Conclusions: Electroacupuncture showed a similar cessation rate in benzodiazepine use to that of non-invasive placebo acupuncture in long-term users during a 4-week gradual tapering schedule. The evidence did not support advantages of electroacupuncture over non-invasive placebo acupuncture on reducing insomnia, anxiety, depression, or other withdrawal symptoms during the gradual tapering schedule. Despite a 40% decrease in the benzodiazepine usage in both groups, the effects may be attributed to the non-specific effects of acupuncture. Trial Registration: ClinicalTrials.gov # NCT02475538. Highlights: Both verum and placebo acupuncture reduce benzodiazepine usage by more than 40%. No significant between-group differences were found in benzodiazepine tapering. The effects may be attributed to the non-specific effects of acupuncture. Both verum and placebo acupuncture are well-tolerated.